Determination of volatile organic compounds in child care centers by thermal desorption gas chromatography-mass spectrometry. Issue 7 (30th January 2018) - Vu, Danh C.; Ho, Thi L.; Vo, Phuc H.; Carlo, Gustavo; McElroy, Jane A.; Davis, Alexandra N.; Nagel, Susan C.; Lin, Chung-Ho
Abstract : Children are among the most vulnerable to certain air pollutants, such as volatile organic compounds. Abstract : Children are among the most vulnerable to certain air pollutants, such as volatile organic compounds. Analysis of indoor air has been analytically challenging and costly. The objectives of this study were to (1) develop and validate a sensitive analytical method for assessing the exposure of children to volatile organic compounds at child care centers and (2) characterize the indoor concentrations of target volatile organic compounds in classrooms at child care centers. The volatile organic compounds were sampled by using thermal desorption samplers and the concentrations of the volatile organic compounds were determined by a thermal desorption gas chromatography-mass spectrometry method. Among the 73 target indoor volatile organic compounds, 47 were identified and quantified in the air samples collected from the selected child care center. The limits of detection and limits of quantitation ranged from 0.001 to 0.123 μg m −3, and 0.002 to 0.406 μg m −3, respectively. The correlation coefficients ( R 2 ) of the calibration were between 0.982 and 0.999. The mean recoveries of the analytes ranged from 87% to 112%. The precision expressed as the coefficient of variation was between 0.6% and 16.2%. The volatile organic compounds identified in our pilot study include a wide range of potential toxic chemicals and endocrine disruptors, such as the ingredients in dry cleaning agents ( e.g., tetrachloroethylene), surfactants ( e.g., butoxyethanol), and personal care products ( e.g., homosalate). Due to the portability, affordability, and flexibility, the developed sampling and analytical method has several advantages over conventional techniques for large-scale multi-position air quality monitoring studies at child care centers.